MORPHOLOGICAL AND SEMANTIC ANGLE OF THE CATEGORY OF TENSE IN ENGLISH AND UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comparative analysis of the morphological and semantic features of the tense category in English and Uzbek. The study examines the ways tense forms are expressed in both languages, their grammatical means, and semantic functions in discourse. It is argued that tense in English is mainly realized through analytical forms, while in Uzbek it is predominantly expressed by synthetic forms. The results of the comparison contribute to minimizing language interference in the process of language learning.